2008
DOI: 10.1158/0008-5472.can-08-1972
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Orphan Nuclear Receptor Nur77-Mediated Apoptotic Pathway by Acetylshikonin and Analogues

Abstract: Shikonin derivatives, which are the active components of the medicinal plant Lithospermum erythrorhizon, exhibit many biological effects including apoptosis induction through undefined mechanisms. We recently discovered that orphan nuclear receptor Nur77 migrates from the nucleus to the mitochondria, where it binds to Bcl-2 to induce apoptosis. Here, we report that certain shikonin derivatives could modulate the Nur77/Bcl-2 apoptotic pathway by increasing levels of Nur77 protein and promoting its mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…Generally, tumorigenesis and tumor progression are strongly associated with abnormal apoptosis. It has been shown that shikonin and its derivatives induce apoptosis of tumor cells [16,19,20] . Our data demonstrate that acetylshikonin could also induce apoptosis of SGC-7901 cells with typical apoptotic alterations, including morphological changes and positive TUNEL assay, DNA fragmentation and apoptotic Apoptosis is a complex process regulated by a variety of factors [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, tumorigenesis and tumor progression are strongly associated with abnormal apoptosis. It has been shown that shikonin and its derivatives induce apoptosis of tumor cells [16,19,20] . Our data demonstrate that acetylshikonin could also induce apoptosis of SGC-7901 cells with typical apoptotic alterations, including morphological changes and positive TUNEL assay, DNA fragmentation and apoptotic Apoptosis is a complex process regulated by a variety of factors [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Total proteins were prepared with a modified radioimmunoprecipitation assay buffer (33). Cytoplasmic proteins were purified with Buffer A [10 mmol/L HEPES-KOH (pH 7.9), 1.5 mmol/L MgCl 2 , 10 mmol/L KCl, and 0.5 mmol/L DTT], whereas nuclear proteins were prepared by resuspending the pellets in high-salt Buffer C [20 mmol/L HEPES-KOH (pH 7.9), 25% glycerol, 420 mmol/L NaCl, 1.…”
Section: Methodsmentioning
confidence: 99%
“…NGFI-B, an orphan member of the steroid/thyroid/ retinoid receptor superfamily of transcription factors in the nucleus (Liu et al 2008;Hamid et al 2008;Liang et al 2007;Eells et al 2000), plays an important role in cell proliferation and apoptosis (Kolluri et al 2008;Tao and Hancock 2008;Winoto 1997;Wilson et al 1991a, b). Recent investigation indicates that in cells treated with apoptosis inducers, NGFI-B translocates from nucleus to cytoplasm.…”
Section: Discussionmentioning
confidence: 99%